An analysis of the judicial approaches in assessing child maintenance applications in Shariah courts / Nurhidayah Hashim and Tim Lindsey - Hashim, Nurhidayah; Tim Lindsey (Academy of Contemporary Islamic Studies, 2016)
In recent years, several parties including custodial mothers have voiced their concern about child maintenance after divorce applications in the Shariah courts. The legal procedure to be followed is said to be difficult and consumed a lot of time and money. In addition, the amount granted in many cases are claimed to be relatively small, not sufficient to cover the needs of the involved children and do not reflect the non-custodial parent's ability to pay. This study investigates the approaches of the Shariah courts in assessing and determining child maintenance applications. By referring to the legal provision in the Islamic Family Law Act 1984, reported and unreported cases from 2002 to 2010 and information received from interviewees, we found that the legal provision for child maintenance is very general with no specific guidelines. As such, judges have to use their discretion in handling the applications which resulted to a range of differing, and sometimes conflicting approaches taken by the courts in verifying the criteria, particularly in ascertaining the needs of the children and the fathers' ability to pay the maintenance for the children. These approaches are not helpful in protecting the best interests of the involved children as the parties affected in the proceedings. This paper therefore, recommends that specific guidelines to be introduced in order to assist judges in assessing child maintenance applications in ways that will better protect the interests of children of divorcing parents.